Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/164913
|View full text |Cite
|
Sign up to set email alerts
|

Association between HMGB1 and COPD: A Systematic Review

Abstract: HMGB1 is an alarmin, a protein that warns and activates inflammation. Chronic obstructive pulmonary disease (COPD) is characterised by a progressive airflow obstruction and airway inflammation. Current anti-inflammatory therapies are poorly effective in maintaining lung function and symptoms of COPD. This underlines the need for finding new molecular targets involved in disease pathogenesis in order to block pathology progression. This review aims to analyse latest advances on HMGB1 role, utilisation, and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…In the present study, the HMGB1 expression in the lung tissues of the COPD model rats was significantly higher than in the control group, indicating that HMGB1 may participate in promoting the onset of COPD. The data are consistent with the studies conducted by Kanazawa et al (30) and Gangemi et al (15). Furthermore, the study by Li et al (31) determined that, compared with in the healthy control population, TRL4 expression in the bronchoalveolar lavage fluid of patients with COPD was significantly high.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the HMGB1 expression in the lung tissues of the COPD model rats was significantly higher than in the control group, indicating that HMGB1 may participate in promoting the onset of COPD. The data are consistent with the studies conducted by Kanazawa et al (30) and Gangemi et al (15). Furthermore, the study by Li et al (31) determined that, compared with in the healthy control population, TRL4 expression in the bronchoalveolar lavage fluid of patients with COPD was significantly high.…”
Section: Discussionsupporting
confidence: 90%
“…In 1999, Wang et al (12) revealed for the first time, to the best of our knowledge, that HMGB1 is involved in sepsis, and can be considered an important inflammatory mediator. A number of previous studies revealed that ulinastatin could inhibit the release of the inflammatory mediator HMGB1 (8,13,14), and, therefore, it could be associated with COPD due to the high expression of HMGB1 in COPD (15). Toll-like receptor 4 (TLR4) is the receptor for HMGB1; the pro-inflammatory role of HMGB1 is closely associated with the TLR4 signal transduction pathway (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous literature review we demonstrated how HMGB-1 levels were augmented in different tissues of smokers and COPD patients [8]. Severe asthma subjects had higher sputum levels of HMGB-1 than moderate and mild patients.…”
Section: Discussionmentioning
confidence: 96%
“…Extracellular HMGB1 binds to cell surface receptors, such as RAGE, which activates the NF-kB pathway. As a consequence, activation of the HMGB1/RAGE/NF-kB pathway increases the expression of a wide variety of inflammatory mediators, escalates the acute inflammatory response, and increases apoptosis in vivo (Gangemi et al, 2015). It is also known that the HMGB1/RA-GE/NF-kB pathway could be regulated by oxidative stress Fig.…”
Section: Discussionmentioning
confidence: 99%